Feasibility of a rapid response mechanism to meet policymakers' urgent needs for research evidence about health systems in a low income country: a case study - Mijumbi, Rhona M (BioMed Central, 2014)
OBJECTIVES: Despite the recognition of the importance of evidence-informed health policy and practice, there are still barriers to translating research findings into policy and practice. The present study aimed to establish the feasibility of a rapid response mechanism, a knowledge translation strategy designed to meet policymakers' urgent needs for evidence about health systems in a low income country, Uganda. Rapid response mechanisms aim to address the barriers of timeliness and relevance of evidence at the time it is needed. METHODS: A rapid response mechanism (service) designed a priori was offered to policymakers in the health sector in Uganda. In the form of a case study, data were collected about the profile of users of the service, the kinds of requests for evidence, changes in answers, and courses of action influenced by the mechanism and their satisfaction with responses and the mechanism in general. RESULTS: We found that in the first 28 months, the service received 65 requests for evidence from 30 policymakers and stakeholders, the majority of whom were from the Ministry of Health. The most common requests for evidence were about governance and organization of health systems. It was noted that regular contact between the policymakers and the researchers at the response service was an important factor in response to, and uptake of the service. The service seemed to increase confidence for policymakers involved in the policymaking process. CONCLUSION: Rapid response mechanisms designed to meet policymakers' urgent needs for research evidence about health systems are feasible and acceptable to policymakers in low income countries. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13012-014-0114-z) contains supplementary material, which is available to authorized users.